2022
DOI: 10.3389/fphys.2022.917886
|View full text |Cite
|
Sign up to set email alerts
|

Persistent dyspnea after COVID-19 is not related to cardiopulmonary impairment; a cross-sectional study of persistently dyspneic COVID-19, non-dyspneic COVID-19 and controls

Abstract: Background: Up to 53% of individuals who had mild COVID-19 experience symptoms for >3-month following infection (Long-CoV). Dyspnea is reported in 60% of Long-CoV cases and may be secondary to impaired exercise capacity (VO2peak) as a result of pulmonary, pulmonary vascular, or cardiac insult. This study examined whether cardiopulmonary mechanisms could explain exertional dyspnea in Long-CoV.Methods: A cross-sectional study of participants with Long-CoV (n = 28, age 40 ± 11 years, 214 ± 85 days post-inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 51 publications
(71 reference statements)
1
17
1
1
Order By: Relevance
“…Persistent dyspnoea has been found to be associated to dysfunctional small airways 3 months after discharge, independently of the severity of disease and parenchymal/radiological sequelae [ 18 ]. However, this is in contrast with the findings of R inaldo et al [ 13 ] and B eaudry et al [ 5 ], who did not find any association between dyspnoea and cardiopulmonary impairment or lung function parameters in COVID-19 patients 3–6 months post-infection. Indeed, L i et al [ 19 ] demonstrated the presence of two different latent phenotypes using a volume-independent contrastive learning model with inspiratory and expiratory chest computed tomography (CT) images in 140 post-COVID-19 patients, one with normal volumes and D LCO but CT signs of air trapping and one with reduced volumes and D LCO but only an interstitial fibrotic like pattern.…”
contrasting
confidence: 96%
See 1 more Smart Citation
“…Persistent dyspnoea has been found to be associated to dysfunctional small airways 3 months after discharge, independently of the severity of disease and parenchymal/radiological sequelae [ 18 ]. However, this is in contrast with the findings of R inaldo et al [ 13 ] and B eaudry et al [ 5 ], who did not find any association between dyspnoea and cardiopulmonary impairment or lung function parameters in COVID-19 patients 3–6 months post-infection. Indeed, L i et al [ 19 ] demonstrated the presence of two different latent phenotypes using a volume-independent contrastive learning model with inspiratory and expiratory chest computed tomography (CT) images in 140 post-COVID-19 patients, one with normal volumes and D LCO but CT signs of air trapping and one with reduced volumes and D LCO but only an interstitial fibrotic like pattern.…”
contrasting
confidence: 96%
“…So far, the origin of dyspnoea and poor exercise performance in l-COVID patients has been investigated in numerous physiological and clinical studies; contrasting findings were obtained mostly because of the heterogeneity of patients, small sample size, variety of applied procedures and methodology [ 4 13 ]. Persistence of dyspnoea in patients that experienced COVID-19 pneumonia or milder forms appears to be unrelated to the degree of disease severity or the residual impairment in lung function, which often corresponds to a mild/moderate reduction in lung diffusion capacity for carbon monoxide ( D LCO ) and, although to a minor extent, of total lung capacity (TLC) [ 5 , 9 , 11 13 ].…”
mentioning
confidence: 99%
“…Um estudo recente mostrou que a dispneia persistente após a COVID-19 somente 13% da amostra havia sido hospitalizada não apresentava relação com comprometimento cardiopulmonar evidente ou intolerância ao exercício. (27) Por outro lado, dispneia persistente, fadiga e intolerância ao exercício já foram relacionadas com desequilíbrio entre a oferta e a utilização de oxigênio periférico, limitação ventilatória ou ventilação disfuncional em amostras com taxas de internação hospitalar de 10-96% durante a fase aguda da COVID-19. (28) Em um estudo no qual foram incluídos apenas pacientes que não estavam em estado crítico (27% dos quais não apresentavam hipoxemia e foram tratados ambulatorialmente), aqueles com dispneia persistente apresentaram menor CVF, DL CO e distância percorrida no TC6, além de aumento da dessaturação durante o exercício, (29) achados consistentes com os nossos.…”
Section: Resultsunclassified
“…17 However, our results are in accordance with a number of studies that also found no link between persistent symptoms and objective cardiopulmonary abnormalities. [18][19][20] Among COVID-19 survivors, cognitive dysfunction, neurological and neuropsychiatric issues appear to be prevalent. In our cohort, cognitive evaluation was performed using the MMSE.…”
Section: Discussionmentioning
confidence: 99%
“…17 However, our results are in accordance with a number of studies that also found no link between persistent symptoms and objective cardiopulmonary abnormalities. 1820…”
Section: Discussionmentioning
confidence: 99%